A study into the ability of SPD to restore the buckling strength and modes of rib stiffened panels with simulated stress corrosion cracks. Issue 1 (6th February 2017) - Jones, Rhys; Matthews, Neil; Peng, Daren; Orchowski, Nicholas
Abstract : Purpose: The purpose of this paper is to describe the results of a combined numerical and experimental study into the ability of supersonic particle deposition (SPD) to restore the load carrying capacity of rib stiffened wing planks with simulated stress corrosion cracking (SCC). Design/methodology/approach: In this context the experimental results reveal that SCC can result in a dramatic reduction in the load carrying capacity of the structure and catastrophic failure via cracking that tears the length of the structure through buckling. A combined numerical and experimental study then reveals how this reduction, in the load carrying capacity can be overcome by using SPD. Findings: This paper is the first to show that SPD can be used to restore the load carrying capacity of rib stiffened structures with SCC. It also shows that SPD repairs can be designed to have only a minimal effect on the local stiffness and hence on the load path. However, care should be taken to ensure that the design is such that premature failure of the SPD does not occur. Originality/value: This is the first paper to show that a thin layer of SPD deposited 7, 075 aluminium alloy powder on either side of the SCC-simulated stiffener has the potential to restore the load carrying capability of a rib stiffened structure. As such it represents an important first step into establishing the potential for SPD to restore the buckling strength of rib stiffened wing panels containing SCC.